2006
DOI: 10.1364/ol.31.000308
|View full text |Cite
|
Sign up to set email alerts
|

Low-loss subwavelength plastic fiber for terahertz waveguiding

Abstract: We report a simple subwavelength-diameter plastic wire, similar to an optical fiber, for guiding a terahertz wave with a low attenuation constant. With a large wavelength-to-fiber-core ratio, the fractional power delivered inside the lossy core is reduced, thus lowering the effective fiber attenuation constant. In our experiment we adopt a polyethylene fiber with a 200 microm diameter for guiding terahertz waves in the frequency range near 0.3 THz in which the attenuation constant is reduced to of the order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
135
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(136 citation statements)
references
References 14 publications
(15 reference statements)
0
135
0
1
Order By: Relevance
“…The transition frequency of the atom is chosen to be midinfrared (MIR), i.e. ω a /2π = 4THz and hence, for experimental purposes the coupling between the distant cavities can be realized by using the modern resources of IR fiber optics, e. g. hollow glass waveguides [20], plastic fibers [21], etc. We choose the range of MIR frequencies in order to limit the thermal reservoir only up to room temperature (300K), which corresponds to a thermal photon.…”
Section: Measuring the Quantum Correlations A Entanglementmentioning
confidence: 99%
“…The transition frequency of the atom is chosen to be midinfrared (MIR), i.e. ω a /2π = 4THz and hence, for experimental purposes the coupling between the distant cavities can be realized by using the modern resources of IR fiber optics, e. g. hollow glass waveguides [20], plastic fibers [21], etc. We choose the range of MIR frequencies in order to limit the thermal reservoir only up to room temperature (300K), which corresponds to a thermal photon.…”
Section: Measuring the Quantum Correlations A Entanglementmentioning
confidence: 99%
“…In the optical regime, there are materials that have low material absorption. However, the terahertz regime is lacking such materials for proper waveguiding, therefore reducing the fractional power inside the dielectric core-the microwire operating regime-is a way of improving the material absorption 15 .…”
Section: Fiber Effective Lossmentioning
confidence: 99%
“…10, 14 Chen et al 15 have recently reported loss values less than 0.01 cm −1 near 0.3 THz in plastic fibers. The concept of THz guided propagation in these fibers is similar to optical nanowire fibers.…”
mentioning
confidence: 95%
“…Terahertz waveguides have consequently also attracted attention, both for distributing the radiation and as functional devices [2]. Apart from hollow metallic and glass waveguides [3,4], the material of choice when making terahertz waveguides is polymer, i.e., poly(methyl-methacrylate) (PMMA) [5], Teflon [6], high-density polyethylene (HDPE) [7,8], and Topas [9]. The reasons for this material choice are that polymers have the lowest loss of most materials in the THz range and they are for the most part easy to machine.…”
mentioning
confidence: 99%
“…Currently there is much research invested in lowering the loss by forcing a large part of the radiation to propagate in air while still being confined to a waveguide, i.e., subwavelength fiber [8], porous fibers [10,11], and hollow-core fibers. Of these, the hollow-core fiber is the least sensitive to outside perturbations, and thus the fiber can be handled without altering the propagation properties.…”
mentioning
confidence: 99%